Fenomena Multikulturalisme Dalam Musik: Sebuah Telaah Elemen Elemen Musikal Non Barat dalam Karya Komposer Musik Barat - Esy Maestro (Komposisi: Jurnal Pendidikan Bahasa, Sastra, dan Seni, 2009)
The study of the music phenomenon has long been an important discussion due to its role in upholding the accretion of the history of literature of the world of music. Among the two poles music’s idealism, which is between European and American, they both have different opinion about multiculturalism. The multiculturalism in the Europe is the unification of the music culture with the lowest integrity level between the music cultures which possibly experience the multicultural process. It means, with the music culture base which just established like music classic, so that the multicultural process will cannot be seen easily from the music which recommended, because its interference usually dissolved is the music substance which intrinsically used, at rhythmic, melodies, form and others.  Meanwhile the multiculturalism phenomenon in the America will offers the explicit structures, which accurately occurs the powerful and influential multiculturalism process. This thing also based on the heterogeneous America’s people as the interference of many cultures by means of the difference music. The multiculturalism music in America also develop faster because in its accretion it influence with the political period and the crime-infested unsafe makes the countries which moves to America feels that they the same. So, it is not surprise if the performance of the African-American music or the America’s World Music will demonstrate the music multiculturalism process which actual and has been growth for a long time. Keywords: the music, multiculturarism, America and Europe